Thoracoscopic resection of functional posterior mediastinal paraganglioma: a case report - Ma, Lin; Mei, Jianong; Liu, Lunxu (Journal of Thoracic Disease, 2014)
A 48-year-old man with posterior mediastinal mass was diagnosed as functional mediastinal paraganglioma during surgical exploration via open thoracotomy in another hospital. The operation was terminated because of severe hypertension when touching the tumor. He was transferred to our center later. After systemic evaluation, the patient was medicated with oral alpha- and beta-blockades, as well as intravenous fluid resuscitation for two weeks. His blood pressure became stable and a second operation was planned. The tumor was removed completely via the thoracoscopic approach, and was finally confirmed as functional paraganglioma by immunohistochemistry. The patient recovered uneventfully after surgery, with no recurrence during one year follow-up visit.